2019
DOI: 10.1002/fsn3.916
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of textural properties and structure of gels prepared from cooked rice grain under different conditions

Abstract: The objective of this study was to investigate the effects of rice variety, water content, and preparation temperature on the textural properties of gels processed from cooked rice grains via high‐speed shear homogenization. Rice gels were prepared from seven high‐amylose rice varieties. The results demonstrated the significant differences in rice gel hardness and hardening rates during storage based on the rice variety used. The proportion of short chains of amylopectin was negatively correlated with the hard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…[ 16 ] It has been reported that B‐type crystal formation should be crucial in starch gelation and retrogradation; it is observed during AM and AP gel formations [ 3–6 ] and regarded as the main reason for the faster starch retrogradation of gel samples containing AP with less amounts of short unit chains. [ 7,18,22 ] The B‐type crystal formation of BD in this study is faster than those of LD, [ 10–12 ] suggesting that it would enable us to search for additives to control starch gelation and retrogradation by a screening of additives which positively or negatively affect the BD association. When AM, instead of BD, is used in water with additives under a condition for B‐type crystal formation, other types of interactions such as V‐amylose formation and inclusion complex formation may occur during association to become insoluble forms.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…[ 16 ] It has been reported that B‐type crystal formation should be crucial in starch gelation and retrogradation; it is observed during AM and AP gel formations [ 3–6 ] and regarded as the main reason for the faster starch retrogradation of gel samples containing AP with less amounts of short unit chains. [ 7,18,22 ] The B‐type crystal formation of BD in this study is faster than those of LD, [ 10–12 ] suggesting that it would enable us to search for additives to control starch gelation and retrogradation by a screening of additives which positively or negatively affect the BD association. When AM, instead of BD, is used in water with additives under a condition for B‐type crystal formation, other types of interactions such as V‐amylose formation and inclusion complex formation may occur during association to become insoluble forms.…”
Section: Resultsmentioning
confidence: 95%
“…In the control sample without borax, the compressive force required to penetrate 20% gradually increases from 0.5 N on the first day of storage to 3.2 N on the fifth day, implying that the double helices in its AP would associate to make the gel harder. [ 18 ] The effect of borax on the retardation of gel hardening is distinct; the loaded values for gels containing 0.1%, 1%, and 10% borax on the fifth day were 2.9, 0.5, and 0.2 N, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rice gels derived from cooked‐rice grain are referred to as cooked‐rice gels and those derived from rice flour are referred to as rice‐flour gels (Figure 1). Cooked‐rice gels were prepared following the method from our previous report (Sasaki et al., 2019). Rice samples (20 g) were weighed in a 100‐mL homogenizer cup, and distilled water (60 g) was added to bring the concentration to 25% (w/w, db).…”
Section: Methodsmentioning
confidence: 99%
“…20) More recently, Okadome et al (1999) adopted a cooking system with 10-g grain with 16-mL water in an aluminum cup to cook in a commercial electric rice cooker. 21) Sasaki et al (2018) used 16-to 27-g grain with water in a 100-mL homogenizer cup to heat at 98 °C to cook in a water bath. 22) Our system with RVA in this study would offer one of the smallest, automatic systems to cook rice grain.…”
Section: Protocol For New Rice-gel Preparationmentioning
confidence: 99%